Six dimensions of research trial acceptability: how much, what, when, in what circumstances, to whom and why?. (September 2018) - Gooding, Kate; Phiri, Mackwellings; Peterson, Ingrid; Parker, Michael; Desmond, Nicola
Abstract: Ethics guidelines emphasise that research should be acceptable to the people invited to take part. However, acceptability is subjective and dependent on context, complicating its assessment and use as an ethical standard. This paper examines the concept of acceptability in relation to parents' perspectives on a paediatric vaccine trial in Malawi. We examined decisions on participation and experiences of the trial through interviews with parents in 41 households invited to enrol their children and participant observation of trial processes. Fieldwork took place in Chikwawa, Southern Malawi from February–October 2016. Parents were not neatly split between those who saw the trial as acceptable and those who did not; instead there were mixed and changing feelings among parents who enrolled their children, and among those who withdrew or did not take part. Some parents agreed to participate but had concerns about the trial, while others expressed satisfaction with the trial but still did not take part. These experiences indicate substantial variation in the nature of acceptance. We describe these variations in relation to six dimensions of acceptability: how acceptable the trial is, what aspects are acceptable, changes over time, circumstances affecting acceptability, variations between people, and reasons for participation or non-participation. The findings illustrate the difficulty of determining whether a trial is sufficiently acceptable to potential participants. We suggest that clarifying definitions of acceptability and examining how acceptability varies in degree, between trial components, over time, and between people and contexts may help researchers generate more nuanced descriptions of acceptability that support responsive and ethical trial design. Highlights: Highlights ambiguity in the idea that research must be acceptable to invited participants. Examines acceptability of a trial to parents invited to enrol their children. Indicates differences between giving consent and seeing a trial as acceptable. Acceptability varies in degree and between times, components, contexts and people. Suggests six dimensions of variation as a guide for future acceptability research.